2008
DOI: 10.1093/annonc/mdm496
|View full text |Cite
|
Sign up to set email alerts
|

KRAS wild-type state predicts survival and is associated to early radiological response in metastatic colorectal cancer treated with cetuximab

Abstract: Background: KRAS mutation status is a candidate marker for predicting survival in patients with metastatic colorectal cancer (mCRC) treated with cetuximab (CTX). Patients and methods:We studied the KRAS mutation status of 113 patients with irinotecan refractory mCRC treated with CTX in clinical trials. A predictive model for objective response (OR), progression-free survival (PFS) and overall survival (OS) was constructed using logistic and Cox regression.Results: OR was seen in 27 of 66 KRAS wild-type (WT) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
450
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(487 citation statements)
references
References 16 publications
27
450
0
10
Order By: Relevance
“…12 Second, a few patients who have tumors with KRAS mutations occasionally respond to anti-EGFR treatment. 1,13,14 The tumors from those responsive patients predominantly harbored codon 13 mutations, and all codon 13 responders have p.G13D mutation. These findings indicate that the KRAS p.G13D mutation and KRAS codon 12 mutations may have a different effect on cetuximab efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Second, a few patients who have tumors with KRAS mutations occasionally respond to anti-EGFR treatment. 1,13,14 The tumors from those responsive patients predominantly harbored codon 13 mutations, and all codon 13 responders have p.G13D mutation. These findings indicate that the KRAS p.G13D mutation and KRAS codon 12 mutations may have a different effect on cetuximab efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, resistance to cetuximab is common, and only 10% to 20% of patients truly benefit from the treatment. 4,5 Recently, it has been widely demonstrated that mutations in v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) codons 12 and 13 are major predictive biomarkers for resistance to cetuximab treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Indeed, KRAS mutations result in constitutively active KRAS proteins that lead to continuous activation of the RAS signaling pathway independently of the upstream stimulation by EGFR ligands. As only patients with wild-type KRAS tumors benefit from therapies with anti-EGFR antibodies, accurate determination of the KRAS mutation status is crucial for ethical and economic reasons.…”
mentioning
confidence: 99%
“…Comme dans la série précédente, aucun patient répondeur n'avait de mutation somatique du gène KRAS. En l'absence de réponse, la progression est rapide et immédiate, c'est-à-dire sans passage par une phase de stabilisation ; symétriquement, en cas de réponse, la diminution de taille des métastases est observable après seulement 8 jours de traitement [1].…”
Section: éTudes Françaisesunclassified